2023
DOI: 10.1007/s00167-023-07318-x
|View full text |Cite
|
Sign up to set email alerts
|

Custom total knee arthroplasty combined with personalised alignment grants 94% patient satisfaction at minimum follow-up of 2 years

Abstract: PurposeThe purpose was to report detailed patient-reported outcome measures (PROMs) and satisfaction rates for computed tomography (CT)-based custom TKA at minimum follow-up of 2 years. The hypothesis was that custom TKA combined with 'personalised alignment' would yield equivalent or better PROMs compared to values reported in systematic reviews and meta-analyses on of-the-shelf (OTS) TKA. Methods Of an initial cohort of 150 custom TKAs, four died (unrelated to surgery), one required a revision, and ive refus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…After promising first results [ 44 ], a large improvement in the KSS was recently shown, with a mean KSS of 94 points after 1 year [ 45 ]. Another study reported a high satisfaction rate of 94% after a mean follow-up of 2.8 years [ 46 ]. KOOS and FJS-12 results in this study were similar or slightly lower than our results after 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…After promising first results [ 44 ], a large improvement in the KSS was recently shown, with a mean KSS of 94 points after 1 year [ 45 ]. Another study reported a high satisfaction rate of 94% after a mean follow-up of 2.8 years [ 46 ]. KOOS and FJS-12 results in this study were similar or slightly lower than our results after 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the different implants, patients with customized, individually made TKA implants had higher expectations, without any effect on patient satisfaction. The impact of customized, individually made TKA implants on patient satisfaction is still controversial, and recent studies have shown conflicting results [11,34,58].…”
Section: Correlation Between Expectations and Patient Characteristics...mentioning
confidence: 99%
“…While reconstructive knee surgeries like total knee arthroplasty (TKA) improve quality of life [10], post‐operative pain is a significant problem with dissatisfaction rates up to 30% [10, 13, 16]. Primary causes include soft tissue impingement due to mis‐fitting femoral prostheses [9]. In China, most available femoral components are based on Caucasian knees, found to be unsuitable for Asian patients [8, 24].…”
Section: Introductionmentioning
confidence: 99%